THE VALIDITY EVIDENCE OF TOEFL TEST AS PLACEMENT TEST - Ayu Liskinasih (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2016)
Abstract: This study is aimed at evaluating the validity of TOEFL test as instrument for placement test. The three sections of the test including listening, structure, reading, and vocabulary were used to measure 96 freshmen basic competences in English, before attending courses. Based on the result of TOEFL test, students were classified into four classes from the highest to the lowest competency levels, namely A, B, C, and D. To measure the correlation level, the two sets of score were compared by using Pearson product moment correlation, the TOEFL score and students’ achievement score. The score of students’ achievement was derived from the final test of Integrated Course. There were 2 language skills and 2 language components that were tested: listening, reading, grammar and vocabulary. The medium positive and significant correlation level (0.41) indicated that TOEFL test was quiet valid to be used as instrument for placement test. However, students’ characteristics and background should be considered to achieve the high and significant correlation level.Keywords: placement test, TOEFL test, and validity